BRIEF HISTORICAL SUMMARY OF THE CAUSANT OF LISTERIOSIS AND ITS PROPERTIES - M.I. Mustafayeva; Tursunova Dilovar Rustam kizi (Journals Park Publishing, 2022)
This article describes the sources of infection of listeriosis, the different ways of pathogen transmission, the polymorphism of clinical manifestations, and the high mortality rate in newborns and immunocompromised people. To learn enough about this, you can learn about the development and study of modern laboratory diagnostics.
Keywords: Listeriosis, infection, ways of transmission, clinical presentation, immunity, bacterial infectious disease, mortality rate, epidemiology, emergency medical care, veterinary medicine.